New Product Varieties and the Measurement of International Prices - Feenstra, Robert C. (American Economic Review, 1994)
The high income elasticity of demand often estimated for U.S. imports may be a spurious result of omitting new product varieties from the import price indexes. The purpose of this paper is to demonstrate how to incorporate new product varieties into a constant-elasticity-of-substitution aggregate of import prices. This method is applied to U.S. imports of six disaggregate manufactured goods. It is shown that the corrected indexes are able to account for part–but not all–of the high income elasticities.